Synergistic benefits from a lignin-first biorefinery of poplar via coupling acesulfamate ionic liquid followed by mild alkaline extraction. (May 2020) - Xu, Jikun; Dai, Lin; Gui, Yang; Yuan, Lan; Zhang, Chuntao; Lei, Yang
Graphical abstract: Highlights: An ally of emimAce and mild alkali to ignite a lignin-first biorefinery on poplar. A food-additive emimAce-driven fractionation to selectively isolate lignin of 37.6%. A slight cellulose expense of 4.47% under the emimAce-oriented environment. emimAce ions are expected to interact with lignin due to their aromatic character. A harvest of 71% lignin, 52% xylan and 90.5% digestibility by the lignin-first path. Abstract: A novel mind-set, termed lignin-first biorefinery, is bewitching to synchronously boost lignin output for entirely lignocellulosic utilization. A lignin-first fractionation, using a food-additive derived ionic liquid (1-ethyl-3-methylimidazolium acesulfamate, emimAce) and mild alkaline pretreatments, was formed for the purposely isolating poplar lignin, whilst delivering a cellulose-rich substrate that can be easily available for enzymatic digestion. The emimAce-driven lignin, alkali-soluble lignin and hemicellulose, and accessible cellulose were sequentially gained. We introduce a lignin-first approach to extract the amorphous fractions, destroy the robust architecture, and reform cellulose-I to II, thereby advancing the cellulose bioconversion from 15.4 to 90.5%. A harvest of 70.7% lignin, 52.1% hemicellulose, and 330.1 mg/g glucose was fulfilled from raw poplar. A structural ''beginning-to-end'' analysis of lignin inferred that emimAce ions are expected to interact with lignin β-aryl-ether due to their aromatic character. It was reasonable to derive benefits from lignin-first technique that can substantially augment the domain of biorefinering.